Coulomb explosion dynamics of ice inside a carbon nanotube - Zosa, Myles Allen H.
This work aims to simulate the coulomb explosion dynamics of ice inside a carbon nanotube. The carbon nanotube proton accelerator devised by Murakami and Tanak comprising a carbon nanotube and hydrogen as a proton source has potential application in cancer therapy and nuclear fusion. The simulations were performed on capped and uncapped carbon nanotubes with ice inside the nanotubes as a proton source. The results show that the proton's energy distribution oscillates in time which is a result of the laser's influence on the system. A number of protons were well collimated as the majority of their speed is supplied by the z- component of the velocity. The capped carbon nanotube displayed increased proton collimation on its uncapped end. This result indicates that capping a nanotube would lead to a more collimated proton beam.